How target-based training affects the passing accuracy of U-13 soccer players - Muhammad Fajar Fathur Rachman Ahmad; Waskito Aji Suryo Putro; Saiful Anwar; Harmaman Harmaman; Leo Pratama (Jurnal Porkes, 2026)
Passing accuracy is a fundamental skill in soccer that often poses a challenge for young players. At SSB Kota Sorong, many U-13 players struggle to direct the ball accurately, making it easy for opponents to intercept. The training methods used so far have tended to be conventional and lack clear objectives, resulting in suboptimal improvements in passing ability. This study aims to determine the effect of target-based passing drills on the passing accuracy of U-13 soccer players at SSB Kota Sorong. The research method employed a one-group pretest-posttest experimental design. The study population consisted of all U-13 players at SSB PS Unimuda. A sample of 15 players was selected using purposive sampling, with criteria of training attendance ≥75% and being injury-free. The instrument used was the low-passing test by Irianto (1995), which had been validated for both validity and reliability. The intervention, consisting of target-based passing drills, was administered over 12 sessions spanning 4 weeks (3 times per week). Data analysis utilized the Kolmogorov-Smirnov normality test and a paired-sample t-test with SPSS 26 at a significance level of α=0.05. The results of the normality test indicated that the data were normally distributed (p>0.05). The mean pretest score was 4.80 (SD = 1.08) and increased to 6.30 (SD = 1.10) on the posttest. The paired t-test showed a calculated t-value of 7.42 > the critical t-value (1.761) with a significance level of 0.000 (p < 0.05). Thus, H0 is rejected and H1 is accepted. In conclusion, target-based passing drills have a significant effect on improving the passing accuracy of U-13 players at SSB Kota Sorong. The average improvement of 1.50 points proves that this method is effective and can be used as an alternative in early-age soccer training programs. This study provides practical contributions for coaches in designing more targeted and measurable training sessions.